IMPROVING STUDENTS’ WRITING SKILL USING PROBLEM-BASED LEARNING - Mairani, Rini (Department of English Education, Universitas Panca Sakti Bekasi, 2022)
The purpose of this classroom action research was to investigate whether Problem-Based Learning (PBL) could effectively address the students’ writing difficulties; to improve their writing skills in the descriptive text as well as to identify the factors that contributed to the improvement. The research participants were 26 students from grade X MIPA 2 of SMAN 6 Kerinci. The study was conducted over two cycles, and data were collected using various instruments, including tasks, tests, observation checklists, field notes, and interviews. The results of the study revealed that the implementation of PBL was effective in improving the student’s writing skills. The PBL process involved giving students a real-life problem to stimulate their writing, group discussion, research, and investigation using worksheets, drafting, writing a descriptive text report, presenting, and evaluating the report as a group. The students’ writing skills were evaluated using test scores, and the average scores significantly improved from 63.1 before the application of PBL to 75.67 after the first cycle and 84.19 after the second cycle. The study also identified several factors that contributed to the improvement, including the quality of the teaching material, the use of appropriate media, and engaging classroom activities. In conclusion, the study demonstrated that PBL was an effective approach to enhancing students' writing skills in the descriptive text at grade X MIPA 2 of SMAN 6 Kerinci.